Online or not? The future of teaching science and research in Africa - case study, Kenya - Mbinda, Phillis Mutheu (Meru: Meru University of Science and Technology, 2022)
The year 2020 forced the whole world to examine its working processes and systems and Sectors. One of the most affected systems was the Educational Sector. This is the most pivotal system which is key to the future of nations and survival of the human race. Africa which has 54 sovereign countries with differing economic status and economies was not spared. Comparative to the developing world, most African countries pre the Covid-19 outbreak, the education sector especially science and research called for stringent and important actions to upgrade to international standards. The closure of schools and institutions of tertiary educations following the pandemic disrupted and threw the sector into disarray. The educators were brought into an abrupt apprehension of the importance and relevance of the internet to the educational sector. But, are the systems in place? This is a process that has many connecting dots and joints which must work hand in hand for the Technological Age at hand for the African Continent.